2017
DOI: 10.2139/ssrn.2910069
|View full text |Cite
|
Sign up to set email alerts
|

Who is Trustworthy? Predicting Trustworthy Intentions and Behavior

Abstract: Existing trust research has disproportionately focused on what makes people more or less trusting, and has largely ignored the question of what makes people more or less trustworthy. In this investigation, we deepen our understanding of trustworthiness. Across six studies using economic games that measure trustworthy behavior and survey items that measure trustworthy intentions, we explore the personality traits that predict trustworthiness. We demonstrate that guilt-proneness predicts trustworthiness better t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 95 publications
0
20
0
1
Order By: Relevance
“…As the question of self-report measures' association with actual behavior and psychological states is a perennial issue in psychological research, particularly when social desirability of responding is a concern (e.g., Crowne & Marlowe, 1960;Paulhus, 1986), it is worth approaching the present results with a degree of caution. However, while actual behavior was not assessed in the present research, previous research has shown that scores on the GASP relate to behavioral outcomes, such as lying for financial gain and trustworthy behavior in interpersonal exchanges (Levine, Bitterly, Cohen, & Schweitzer, 2018).…”
Section: Limitationsmentioning
confidence: 90%
“…As the question of self-report measures' association with actual behavior and psychological states is a perennial issue in psychological research, particularly when social desirability of responding is a concern (e.g., Crowne & Marlowe, 1960;Paulhus, 1986), it is worth approaching the present results with a degree of caution. However, while actual behavior was not assessed in the present research, previous research has shown that scores on the GASP relate to behavioral outcomes, such as lying for financial gain and trustworthy behavior in interpersonal exchanges (Levine, Bitterly, Cohen, & Schweitzer, 2018).…”
Section: Limitationsmentioning
confidence: 90%
“…Multiple studies of cultural differences in negotiation rely on this theory (Gelfand et al, 2013;Gelfand and Cai, 2004;Kern et al, 2012;Morris and Gelfand, 2004). Negotiation is a IJCMA 32,5 social decision-making process in which parties are interdependent and negotiators rely on knowledge of themselves, the other party and the context to make trust-related decisions (Levine et al, 2018;Mayer et al, 1995). In negotiations, the context can make certain cultural knowledge more salient and more accessible for negotiators, thereby affecting their attitudes and behaviors.…”
Section: Theoretical Background and Hypothesis Developmentmentioning
confidence: 99%
“…Trustworthiness is the part of trust that looks at one's likelihood to do what one has promised-will a negotiator carry out his or her commitments. 114 It logically follows that when negotiators can trust one another, the negotiation itself WHAT'S SEX GOT TO DO WITH IT 939…”
Section: Why This Skill Matters In Negotiationmentioning
confidence: 99%